Immunization of White Mice against Hydatid Cyst Using Antigen B and Excretion - Secretion Antigen - Ali, W. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this study was  toward the possibility of producing antigen that has  the ability to stimulate the immune response against the infection with the  hydatid cyst. To do so antigens were extracted from sheep hydatid cyst fluid of  Echinococcus granulosus .These were: 1- The hydatid cyst fluid called antigen B. 2- Excretion-secretion called ES antigen. 3-B/ES antigen is a mixture (1:1) of the above two antigens. Three concentrations   (15, 30 and 60 Âµg/ml) from antigen B/ES were prepared to immunize the white mice (males)  with 20 Âµg/gr body weight and one booster dose  (10 Âµg/gr) to stimulate immunity.      The efficiency of these antigen concentrations against secondary infections was investigated by the calculation of the reduction in percentage of cysts numbers        The results revealed that the reduction percentages of cyst in immunized group were 91.5% , 92.3% and  100%  for concentration antigen 15, 30 and 60Âµg/g for    Thr Immunized groups respectively.. There was a significant difference (pâ‰¤0.05) between and the positive control group infection. After 45 days of infection, the sensitivity test showed that the highest cellular immune response occurred after three hours of the injection of the B/ES antigen in the left footpad of the animals. This response was measured through the increase in the thickness of the footpad. The reaction was clear in the positive control and in the infected immunized animals. When the test was repeated after 90 days of the infection, the results were similar to the above, but the reaction was more acute than in the first time especially in the positive control groups of mice.